Association of Vaginal Progesterone Treatment With Prevention of Recurrent Preterm Birth. Issue 4 (April 2023) - Nelson, David B.; Lafferty, Ashlyn; Venkatraman, Chinmayee; McDonald, Jeffrey G.; Eckert, Kaitlyn M.; McIntire, Donald D.; Spong, Catherine Y.
ABSTRACT: One of the foremost public health concerns in obstetrics is preterm birth (PTB), which carries substantial consequences for infants, families, and societies that are well-documented. Affecting approximately 15 million births worldwide, PTB is a leading cause of death for children younger than 5 years. Unfortunately, identifying strategies to reduce PTB has proven challenging, in part because multiple causes exist for spontaneous PTB. It is widely recognized that a history of PTB is one of the strongest risk factors for recurrence. It has been suggested that the onset of parturition occurs because of functional progesterone withdrawal, which has led to the use of progestogens as an agent for PTB prevention efforts. Currently, both the Society for Maternal-Fetal Medicine and the American College of Obstetricians and Gynecologists support progestogen therapy for prevention of recurrent PTB in select patients with singleton pregnancies. The purpose of this study was to report on the effectiveness of vaginal progesterone vaginal progesterone for PTB prevention in a single inner-city practice. The primary aim was to evaluate the association of vaginal progesterone with PTB prevention at a gestational age of 35 weeks or less. The authors hypothesized a reduction of recurrent PTB with vaginal progesterone–treated patients as compared with historical control subjects with similar numbers and frequency of prior PTBs. Additional examinations included clinical outcomes and therapy associated with severity of recurrent PTB, progesterone blood levels, and medication adherence. This study utilized an inception, cohort study format in which all clinic patients were offered vaginal progesterone beginning on May 15, 2017. A comparison of recurrent PTB in patients treated with vaginal progesterone with a historical cohort prior was the outcome of interest. Each patient underwent detailed obstetric history, including the number of confirmed previous births, perinatal outcome, reason(s) for PTB, gestational age at PTB, and birth weight. Patients with medically indicated PTB (such as those due to pregnancy-related hypertension) were excluded. Only the first pregnancy outcome was analyzed for patients with more than 1 pregnancy during the study period. Because of variation in risk levels for PTB based on race and ethnicity, this information was collected by research staff using patient self-report. Patients with prior spontaneous PTB at 35 weeks or less due to rupture of membranes or spontaneous labor during any prior pregnancy were eligible. Therapy included 90 mg of vaginal progesterone (8%, nightly) between 16 weeks 0 days and 20 weeks 6 days until 36 weeks and 6 days (or delivery). The primary outcome was PTB recurrence at 35 weeks or less for patients given vaginal progesterone as compared with the 3:1 matched historical cohort (untreated). An intention-to-treat principle was the basis for this analysis. Secondary outcomes included the following: (1) association of PTB recurrence rate with vaginal progesterone treatment adherence (defined as 80% or more of doses), (2) comparison of specific patients' gestational ages at prior PTBs with the gestational age at delivery following vaginal progesterone treatment, (3) ascertainment of whether PTB was associated with serum progesterone levels among vaginal progesterone–treated patients, (4) comparison of pregnancy outcomes for patients declining the use of progestogens, and (5) pregnancy outcomes during the era of 17-α hydroxyprogesterone caproate (17-OHP-C) use (2012–2017) as compared with the contemporary vaginal progesterone use and study. In the historical cohort, when progestogen was not in use, the PTB rate at 35 weeks or less was 16.8% (1394 of 8278). Between May 15, 2017, and May 7, 2019, 417 study patients were identified from a pool of 2883. The overall rate of recurrent PTB in this group was 24.0% (100 of 417) in the vaginal progesterone cohort compared with the expected historical rate of 16.8%. Further analysis indicated that adequate adherence was not associated with lower rates of recurrent PTB, and the use of vaginal progesterone was not associated with a decrease in the overall rate of recurrent PTB when examined according to intention-to-treat analysis. In addition, the PTB recurrence rates were not lower with the vaginal progesterone treatment when analyzed according to the specific sequence of prior PTBs and term births. The authors note that this study may lack generalizability because of its nature as a single-center report. The predominantly Hispanic and non-Hispanic Black patients with obesity served at Parkland Hospital represent a medically indigent population. In addition, therapy adherence was low, as 80% of participants discontinued therapy because of reported adverse effects from medication. However, blood progesterone levels failed to suggest differing therapy responses as compared with elevated physiological levels of normal pregnancy. In fact, the study results suggest that vaginal progesterone may increase recurrent PTB rates in this population. Finally, vaginal progesterone treatment in patients with a short cervical length was beyond the scope of this analysis. Vaginal progesterone treatment of patients with current singleton pregnancies within this prospective cohort study found that this intervention did not decrease the rate of recurrent PTB as compared with historically matched control subjects for sequence and number of prior PTBs. It additionally did not find an association with clinical improvement in outcomes due to adherence to medication, progesterone blood levels, or severity of PTB recurrence. In light of these findings, the authors recommend against offering vaginal progesterone for prevention of recurrent PTB using the personal PTB history alone as a basis.